RANCANG BANGUN SISTEM INFORMASI POTENSI AGROINDUSTRI BERBASIS SINGKONG DI KABUPATEN JEMBER - Yuli Wibowo; Bambang Herry Purnomo; Elvina Putri Wicaksono (Agroindustrial Technology, University of Trunojoyo Madura, 2015)
Jember Regency is one of the regency in East Java Province that has some potential comodity in agriculture sector, one of them is cassava. Cassava-based agroindustry in Jember Regency have a large ammount and spread in several sub district. Statistical data about the agroindustry potency include ammount, type, distribution and information overall not yet processed become the holistic and comprehensive information, still packed in textual and until now the attractive, informative, accessible and renewed information system which supply the information about the cassava-based agroindustry in Jember Regency is not available. The purpose of this study is to design information system for identification of cassava-based agroindustry. This study give an information system that will supply the information about cassava-based agroindustry in Jember Regency, include agroindustry profile, raw materials profile and the other information related to agroindustry in the form of graphic that more attractive, informative, accessable and give facilities for related parties in doing information renewed by quickly and properly so cassava-based agroindustry in Jember district can be developed.